2021
DOI: 10.1089/g4h.2020.0042
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Serious Games in Dentistry: A Scoping Review

Abstract: Objective: Over the past decade, serious games (SGs) have played a growing role in medical education and health promotion; however, little is known about their use in the field of oral health. This study provides a comprehensive synthesis about SGs developed for training oral health professionals or for health promotion in oral health. Material and Methods: A systematic search was conducted. The following electronic databases were reviewed: MEDLINE (1966 to September 2019), Embase (1980 to September 2019), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In game‐based learning, a player engages in the game's activity and loses the sense of effort and repetition, and gains knowledge and satisfaction from solving the game's challenges. Motivation and engagement are fundamental elements to framing learning from gaming experience 5 …”
Section: Resultsmentioning
confidence: 99%
“…In game‐based learning, a player engages in the game's activity and loses the sense of effort and repetition, and gains knowledge and satisfaction from solving the game's challenges. Motivation and engagement are fundamental elements to framing learning from gaming experience 5 …”
Section: Resultsmentioning
confidence: 99%
“…An emerging application in dentistry is the use of serious games (SGs). These games are increasingly utilized for medical education, training and informative purposes to convey oral health messages [ 73 75 ]. In this systematic review, the overall quality of the evidence is good.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that cartoon-animated audiovisual aids and game-based education implemented for schoolchildren are powerful tools for educating and providing thought-stimulating methods of learning [ 16 , 17 ]. The use of fun-based learning interventions (connect the dots games [ 1 , 18 ], crosswords and quizzes [ 3 ], flashcards [ 1 ], snakes and ladders [ 19 , 20 ], augmented reality board games [ 21 ], video games [ 22 , 23 ], smartphone oral hygiene applications [ 24 ], and animated audiovisual resources [ 25 ]) have been suggested to be a perfect motivating tool to encourage children to take part in self-care activities. The use of gaming in OHE can be a good alternative for educating basic health concepts, thereby, strengthening cognitive development and confidence [ 26 ].…”
Section: Discussionmentioning
confidence: 99%